2014
DOI: 10.1007/s10967-014-3016-2
|View full text |Cite
|
Sign up to set email alerts
|

Thin layer spectroelectrochemical (RVC-OTTLE) studies of pertechnetate reduction in acidic media

Abstract: The electroreduction of the pertechnetate ions has been examined in sulfuric acid solutions (0.5–4 M) using optically transparent thin layer spectroelectrochemical (RVC-OTTLE) cell. Soluble Tc(III), TcO2+ and [Tc(μ-O)2Tc]3+/4+ species with absorption bands at 420–450, 400, and 502 nm, respectively, were found to be formed during the reduction of TcO4− ions. The strongly acidic medium was found to stabilize technetium ionic forms with lower oxidation states. Spectroelectrochemical measurements performed in 4 M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…Simultaneously recorded spectroscopic signal does not reveal significant decrease in concentration of TcO 4 − , in agreement with our previous results [ 20 ]. Various products of pertechnetates reduction below 0.4 V are proposed in the literature, including TcO 2 ·×H 2 O [ 27 ], Tc(IV)/Tc(III) species [ 28 ] or to Tc(III) which can syn proportionate with Tc(VII) ions to Tc(IV) [ 29 ].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Simultaneously recorded spectroscopic signal does not reveal significant decrease in concentration of TcO 4 − , in agreement with our previous results [ 20 ]. Various products of pertechnetates reduction below 0.4 V are proposed in the literature, including TcO 2 ·×H 2 O [ 27 ], Tc(IV)/Tc(III) species [ 28 ] or to Tc(III) which can syn proportionate with Tc(VII) ions to Tc(IV) [ 29 ].…”
Section: Resultssupporting
confidence: 92%
“…Stability of technetium species at moderate oxidation states is the key factor in understanding technetium behavior in the PUREX process. In my earlier study [ 20 22 ] I applied an optically transparent thin layer cell (RVC-OTTLE) in studies of electrochemical behaviour of technetium compounds. We found that stability of non-complexed technetium species in sulfuric acid solutions decreases in the following order TcO 4 − > [Tc 2 O 2 ] 3+ > TcO 2+ > TcO + (or Tc 3+ ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much more stable than TcO 2+ in acidic solutions are dimeric [Tc(µ-O) 2 Tc] 3/4+ or polioxopolimetallic, Tc 3 O 4 4+ , ions [10]. These ions are characterized spectroscopically by the band at 502 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The standard redox potential of this reaction equals 0.512 V vs. SHE. In sulfuric [10] or nitric [14] acid solutions also Tc(III) ionic species were identified. Tc 3+ or TcO + ions (till now the structure is unknown) are characterized spectroscopically by visible band at 440 nm and can be distinguished from oxotechnetium(IV) showing a band with a maximum at 400 nm.…”
Section: Introductionmentioning
confidence: 99%